Variation of Chemical Components in Bintangur (Callophyllum inophyllum) Wood along Stem Position and Its Potential Industrial Uses - Hikma Yanti; Alkhadi; Muhammad Dirhamsyah; Ahmad Yani (Forest and Nature, 2025)
This study investigates the axial variation of major chemical constituents in bintangur wood (Calophyllum inophyllum), a species native to Indonesian peat forests, with emphasis on its industrial applicability. Wood samples were collected from three stem positions—base, middle, and top—to quantify extractives, holocellulose, alpha-cellulose, hemicellulose, and lignin content using the Technical Association of the Pulp and Paper Industry (TAPPI) standard methods. The results revealed a notable chemical gradient along the tree axis. Holocellulose (65.76–72.28%) and alpha-cellulose (44.56–49.61%) increased toward the upper stem, indicating enhanced suitability for pulp, paper, and bioethanol conversion at the tip region. In contrast, ethanol-benzene extractives peaked at the middle (7.26%) and declined at the tip (4.52%), while lignin exhibited a non-linear pattern, ranging between 25.47–28.64%. The moderate lignin content supports potential applications for charcoal, adhesives, phenolic derivatives, vanillin synthesis, and engineered wood products. Meanwhile, the relatively high extractive fraction suggests additional prospects for natural preservatives, essential oils, dye sources, and marine-grade timber. Overall, the distinct axial variability in chemical composition highlights the importance of stem-position-based processing optimization and demonstrates the feasibility of bintangur as a versatile raw material for biorefinery-based utilization. These findings provide baseline knowledge supporting future industrial development and valorization strategies for this under-exploited tropical hardwood.